Colbert and Governmental Control of Industry in Seventeenth Century France - Usher, Abbott Payson (The Review of Economics and Statistics, 1934)
COLBERT AND HIS TIME COLBERT was by temper an administrator; ordinarily shrewd in his judgments of current problems, and energetic in accumulating precise information. Though he certainly possessed genuine convictions, he was ever ready to temporize and to adapt his policies to local conditions. Many aspects of his reforms were essentially liberal in character, because his administrative reorganization necessarily led him to destroy obsolescent feudal rights and privileges, and to remove the numerous impediments to freedom of internal trade that were created by the officials of provinces, towns, and villages. His correspondence discloses such flexibility of thought on all these matters that any reader will be quickly convinced that the full content of Colbert's mind cannot be rendered in the catchwords of mercantilism. His industrial policy likewise discloses considerable breadth of mind. There is so much emphasis on advanced instruction, training in the fine arts, and upon technology that one must be careful not to impute to Colbert indifference to the achievements of the individual. In discussing his position in respect of the merits of individualism and collectivism it is necessary to bear in mind that in his day France was already beginning to feel the stress of competition with England and Holland. There were changes in the valuation of her economic resources that constituted a threat to her continued prosperity, though they were not at that moment an explicit factor. Colbert lived in a region that had really reached the height of its development. It was a society, too, already deeply affected by the peculiarly insidious inertia of a venal bureaucracy dominated by persons holding life interests in their salaries, irrespective of the continuance of the functions of the office. Many families of wealth looked upon their positions in the judiciary as estates by inheritance, subject to the payment of specified fines. It -was a society characterized by the courtier and the sycophant, dominated by ambitions for the secure social position conferred by land and offices. Industry and commerce were at best merely means of purchasing social security, and neither industry nor trade was expanding rapidly enough to inspire much hope or to foster a general spirit of enterprise and adventure. It was a society deeply conscious of its age; the individual looked for shelter and security rather than for opportunities to do new things or to exploit new fields. Neither the appeal of India, nor the romance of the New World, really stirred this blase and timorous society. Colbert's judgment of the possible contribution of the individual to society must thus be read in its context. His policies express only his estimate of the possible achievement of the Frenchmen that he knew, both bourgeois and nobles. To conclude, as he did, that the state might contribute much to the economic development of this society was shrewd realism. We must recognize also that Colbert was by no means the first to formulate the policies that are commonly associated with his name. Scarcely aniy phase of his policies or administrative reforms was significantly original. His financial reforms were foreshadowed by the projects laid before the States General in i6I3. The administrative system embodied in the Intendants was merely the culmination of a process of growth that reached far back into the sixteenth century. The industrial policy is foreshadowed by the edicts of I58i and I597 and' by the systematic schemes of Laffemas for the development and encouragement of industry. Many projects of economic reorganization were entertained by Richelieu. Despite these extensive plans, there was little effective accomplishment before Colbert's time. In some instances edicts had been issued with all possible solemnity; in other cases, schemes were worked out on paper but never given legal sanction. Whatever the history of the various projects, actual accomplishment was negligible. Colbert gave practical effect to concepts of royal authority and to policies that had been held since the later phases of the Wars of Religion.